Modeling cell osmotic behavior during cooling and water crystallization - Pakhomov, Oleksandr; Kovalenko, Igor; Poliakova, Hanna; Gurina, Tetiana; Bozhok, Galyna (Problems of Cryobiology and Cryomedicine, 2026)
Selection of cryopreservation parameters, such as cooling rates, is crucial for the successful preservation of cell suspensions. The objective of this study was to assess the impact of cooling rates and nucleation on the survival of testicular interstitial cells (ICs) and to model cell osmotic behavior based on the Kedem-Katchalsky formalism during water crystallization. The ICs were cooled in the serum-free medium supplemented with 0.7 M DMSO and 100 mg/ml dextran 40 (0.7DMSO+D40). The modeling of IC osmotic behavior in the medium, based on experimentally determined water and DMSO membrane permeability coefficients and activation energies, revealed the potential to increase the cooling rate from the "standard" 1 °C/min. This possibility was tested experimentally using higher cooling rates of 2, 5, and 10 °C/min. A cooling rate of 2 °C/min, combined with controlled nucleation parameters, was shown to be beneficial for preserving ICs in 0.7DMSO + D40. The approach including modeling, the use of defined serum-free compositions, controlled nucleation and optimization of cooling rates, can be applied to other cell types cryopreserved in multicomponent cryopreservation media. Probl Cryobiol Cryomed. 2026; 36(2): 79—88